2019
DOI: 10.1021/acscatal.9b01628
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplementary Chemoenzymatic Pictet–Spengler Reactions for Formation of Rare Azepino-indole Frameworks: Discovery of Antimalarial Compounds

Abstract: Strictosidine synthase (STR1) catalyzes a Pictet–Spengler reaction (PSR) forming strictosidine, a likely biosynthetic key to all higher plant monoterpenoid indole alkaloids. Increasing the biocatalytic capacity of the enzyme may make it a powerful tool for generation of compound libraries with enhanced structural diversity and pharmaceutical activity. Herein two production routes of a rare class of azepino­[3,4,5-cd]-indoles are developed: a complementary STR1-dependent chemoenzymatic and stereoselectively che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…falciparum, implying the configuration of C-4 position could influence the activity. [69] The β-carboline derivatives 29a,b exhibited 71.79%…”
Section: Indole Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…falciparum, implying the configuration of C-4 position could influence the activity. [69] The β-carboline derivatives 29a,b exhibited 71.79%…”
Section: Indole Hybridsmentioning
confidence: 99%
“…The antiplasmodial activity of 4α( S )‐configurated azepino[3,4,5‐ cd ]indole 28a (IC 50 : 3.4 µM) was superior to that of its 4β( R )‐configurated epimer 28b (IC 50 : 6.1 µM) against CQS 3D7 strain of P. falciparum , implying the configuration of C‐4 position could influence the activity. [ 69 ] The β‐carboline derivatives 29a , b exhibited 71.79% and 86.17% inhibition of P. berghei schizont maturation respectively at a concentration of 5 µg/ml, whereas the reference chloroquine exhibited 90.66% inhibition at 10 µg/ml. [ 70 ] These two hybrids did not cause any deaths and behavioral changes at a dose of >2.5 g/kg in the in vivo acute toxicity evaluation, suggesting their excellent safety profile.…”
Section: Indole Hybridsmentioning
confidence: 99%
“…Inspired by the previously reported phosphate‐mediated PSRs, we embarked on the investigation of azepino‐indole formation by treating 2‐(1 H ‐indol‐4‐yl)ethanamine ( 1 a ) with benzaldehyde ( 2 a ) in potassium phosphate buffer (KPi, pH=7.0) at 50 °C. The desired product 3 aa was obtained in a good yield of 72% (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…− In addition, a special PSR was realized in toluene at reflux with tryptophan methyl ester derivatives as the amine source, without the aid of any catalyst . Very recently, we disclosed a strictosidine synthase (STR1)‐catalyzed and potassium phosphate (KPi)‐mediated stereocomplementary PSR of 2‐(1 H ‐indol‐4‐yl)ethanamine and secologanin to give complex indole alkaloids with aezpino‐indole frameworks . These observations demonstrated that the PSR conditions could be continuingly improved for more sustainable performance.…”
Section: Introductionmentioning
confidence: 99%
“…[5,7] In nature this condensation reactioni sc atalysed by enzymes called Pictet-Spenglerases, [8] which are sub-categorised according to their substrates. For instance, norcoclaurine synthases( NCSs) [9] prefer dopamine as amine substrate,w hile strictosidine synthases (STRs) [10] acceptt ryptamine and its derivatives, leadingt ob-carbolines as products. While for norcoclaurine synthases ab road scope of carbonyl substratesh as been reported, [9] it has only recently been shown that STRs accepts mall aliphatic aldehydes besides the natural, highly functionalized aldehyde secologanin (4c, Figure1)and itsa nalogues.…”
mentioning
confidence: 99%